“De colombia con amor”: a comida no processo de construção de memória coletiva das famílias de refugiados colombianos em Santa Maria, RS - Erazo, Diana Patricia Bolaños (2023)
This thesis presents a discussion about the role of Colombian food in the construction of memories among and with families of Colombian refugees resettled in the city of Santa MariaRS. In this specific context of mobility, it was observed the cultivation and harvest of spices, the search for ingredients in the markets, the negotiation of ingredients, the preparation, distribution and, finally, the sharing of food collectively as a way to narrate and relocate in the world after the traumatic experience of expulsion from the country of origin. A discussion is thus developed from the concepts of the anthropology of food, mobilities and displacements, and memory studies, to understand the communicative power that food has; evoking feelings and memories of the country of origin, creating transnational bonds that go beyond the claim of a national identity, and producing habits that are transmitted from generation to generation. The research was developed between March 2019 and December 2022, however, some of the information to which I refer here was previously recorded through my experience as a Colombian in Santa Maria and my direct participation in these networks of Colombians. Through ethnographic research, and the use of participant observation, interviews, conviviality in person and in virtual social networks, the commensalities, sociabilities and narrative constructions made possible through Colombian food in Santa Maria were known. It is concluded that the spaces of commensality are events in which the social body is reproduced, the country of origin is remembered, and past moments of scarcity are resigned. The observation of food in the refuge context showed that keeping the food practices as in Colombia was a strategy to search for meaning in everyday life and a way to remember a country of origin in peace, that is, when food is brought to the table, on several occasions, it is in charge of mediating the process of insertion and adaptation in the city of the interior of Rio Grande do Sul and a way to talk about pain and loss without using words.